Utilization Of Antibiotics In Patients With Urinary Tract Infections: Utilization Of Antibiotics - Usha Panta (STIKes Mandala Waluya Kendari, 2022)
Objectives: This study aims to investigate the utilization of antibiotics among the patients attending in Silverline Hospital, Lekhnath Marg, Balaju, Kathmandu-44600, Nepal. Methods: A hospital based cross sectional study was conducted in between June to September, 2022. A standard questionnaire was prepared, to conduct the survey based on patient’s demographic data such as which utilization of drug, age, gender, therapy and medication. Results: Out of 111 patients, antibiotics Levofloxacin is highly prescribed to the patients. It is prescribed to 92 (82.90%) people. Cefixime is prescribed for 37 (41.07%) people, Ciprofloxacin is prescribed for 29 (26.12%) patients, Ofloxacin is prescribed for 5 (4.5%) and Nitrofurantoin is prescribed for least for number of people and it is prescribed for 4 (3.6%) patients. Conclusion: Fluroquinolones and Cephalosporins were the most commonly prescribed antibiotics in this study. Culture sensitivity test was carried out only in a limited number of cases, and present findings together with previous ones are suggestive of the need for periodic monitoring of antibiotic sensitivity pattern of the bacterial isolates to provide effective treatment and thereby to make it more cost effective particularly in the developing countries like Nepal. The continuous monitoring and reporting of prescribing pattern of antibiotics will surely help the physicians for effective treatment.